ZrO2 doped CMA material preparation and structure and function integrated regulation and control method

The preparation of ZrO2-doped CMA material through one-step sintering method solves the problems of complex and high cost in the preparation process of CMA material, and realizes integrated control of structural functions and performance improvement. It is suitable for different parts of industrial boiler furnace bodies.

CN119263852AActive Publication Date: 2025-01-07UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202411409161.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The preparation process of existing CMA materials is complex and costly, making it difficult to achieve integrated regulation of structural functions, which limits its large-scale application in the field of industrial furnace lining.

Method used

ZrO2-doped CMA material is prepared by one-step sintering method. By adjusting the proportion of alumina, calcium oxide, magnesium oxide and the addition amount of zirconium dioxide, the firing temperature and insulation time are controlled, so as to achieve uniform distribution of C2M2A14 phase and the control of volume density. , improve melting point and reduce water absorption.

Benefits of technology

The preparation of ZrO2-doped CMA material with adjustable performance is realized, which reduces production costs and cycles, can be used for the preparation of refractory materials of different densities, and is suitable for different parts of industrial boiler furnace bodies, improving the refractory performance of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263852A_ABST
    Figure CN119263852A_ABST
Patent Text Reader

Abstract

The embodiment of the invention discloses a ZrO2 doped CMA material preparation method and a structure and function integrated regulation and control method thereof. The method comprises the following steps: S1, mixing an aluminum oxide source, a calcium oxide source and a magnesium oxide source according to a set proportion to obtain a mixed source material, and adding an additive zirconium dioxide into the mixed raw material to obtain a raw material mixture; wherein the particle sizes of the alumina source, the calcium oxide source and the magnesium oxide source are equivalent, and the mass ratio of the zirconium dioxide to the mixed source material is not greater than 4wt%; s2, stirring and mixing the raw material mixture, and adding a water binder to obtain a uniformly mixed material; wherein the mass ratio of the water to the raw material mixture is 5-50%; s3, carrying out compression molding on the uniformly mixed material under the pressure of 80-120 MPa to obtain a green body; and S4, firing the green body in an air atmosphere at 1650-1750 DEG C to obtain the ZrO2 doped CMA material. The content of the C2M2A14 phase in the CMA material can be regulated and controlled between 80% and 100% by regulating and controlling the doping amount of ZrO2, the firing temperature and the heat preservation time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a ZrO2-doped CMA material and a method for integrating structural function thereof. Background Art

[0002] In order to achieve energy saving and consumption reduction in the steel smelting process, the lining materials of industrial furnaces are usually composed of multiple layers, with heavy materials used in the working layer and porous insulation materials used in the insulation layer. The working layer is in direct contact with the molten steel, and its performance and application are directly related to the efficiency and safety of steel industry production, which requires the refractory materials of the working layer to have excellent high temperature resistance, stability, thermal shock resistance and slag erosion resistance. The insulation layer uses porous insulation materials to reduce the heat loss of the furnace body, make the temperature distribution of the furnace body uniform, and prevent damage to the furnace structure. Due to the differences in the properties of different layers of materials, cracks and shedding are easy to occur during use. Using materials with similar components as the working layer and insulation layer of the furnace body can ensure that the industrial furnace has efficient thermal insulation performance while operating safely and stably, thereby reducing heat dissipation loss and heat storage loss to achieve energy saving.

[0003] A12O3-MgO-CaO ternary system refractory materials have excellent performance in structure and function, and have become a hot spot in the research of green high-temperature refractory materials. Among them, the typical high-melting-point compounds in the aluminum-rich part of the A12O3-MgO-CaO ternary system are magnesium aluminum spinel (MgAl2O4, abbreviated as MA) and calcium hexaaluminate (CaAl 12 O 19 , abbreviated as CA6) has the advantages of high melting point, strong stability, strong thermal shock resistance, low wettability to molten metal / slag, etc., and is widely used in steel, petrochemical and aluminum industries. However, due to the large difference in the stable region and crystallization habits of CA6 and MA, it is relatively difficult to synthesize dense CA6 / MA composite materials, which greatly limits the integrated design and application of industrial furnaces based on CA6 / MA composite materials.

[0004] Ca2Mg2Al 28 O 46 (Abbreviated as C2M2A 14 ) and CaMg2Al 16 O 27(abbreviated as CM2A8) collectively referred to as CMA, are two limited solid solutions of MgO in CA6, with the excellent properties of MA and CA6, and have been preliminarily applied in the fields of clean steel smelting, high-temperature alloy smelting, etc. However, the current preparation process of CMA materials is complex and the cost is high, which seriously limits its industrial application. On the one hand, the raw materials used to produce CMA are mainly alumina source, calcium source and magnesium source. The uniformity of the mixing of the three raw materials determines the physical properties and purity of the prepared CMA material. The preparation of CMA materials usually adopts wet mixing method for mixing, but when wet mixing, it is necessary to first mix Al2O3, CaCO3 and MgCO3 powders evenly, and then dry, crush and press them into green bodies, which greatly increases the preparation process and preparation cost. In addition, due to the differences in powder density and particle size, the mixed powder obtained by wet mixing is also very easy to stratify during the drying process.

[0005] On the other hand, CMA materials can be prepared by methods such as electric melting, hot pressing and two-step sintering. Although these methods can produce relatively dense CMA materials, they all have disadvantages such as complex processes, long production cycles and high energy consumption, making it difficult to achieve industrial preparation.

[0006] The one-step sintering method can effectively shorten the preparation process and reduce production costs, and has been widely used in the industrial preparation of refractory materials. However, it is still difficult to achieve integrated regulation of the structure and function of CMA materials, which greatly limits its large-scale application in the field of industrial furnace linings. Summary of the invention

[0007] In view of this, on the one hand, some embodiments disclose a method for preparing a ZrO2-doped CMA material and integrating its structure and function, comprising the steps of:

[0008] S1, an aluminum oxide source, a calcium oxide source and a magnesium oxide source are mixed in a set ratio to obtain a mixed raw material, an additive zirconium dioxide is added to the mixed raw material, and a raw material mixture is obtained by a mixer; wherein the particle sizes of the aluminum oxide source, the calcium oxide source and the magnesium oxide source are equivalent, the mass ratio of zirconium dioxide to the mixed source material is not more than 4%, and the mixing time of the mixer is 1 to 6 hours;

[0009] S2, stirring and mixing the raw material mixture, adding a water binder, and obtaining a uniformly mixed material; wherein the mass ratio of water to the raw material mixture is 5 to 50%;

[0010] S3, the uniformly mixed material is pressed and molded at a pressure of 80-120 MPa to obtain a green body;

[0011] S4, the green body is fired at 1650-1750℃ in air atmosphere and kept warm for 3-10h to obtain ZrO2-doped CMA material; ZrO2-doped CMA material contains only C2M2A 14and CM2A8 phases, Zr ions are uniformly distributed in CMA grains; C2M2A 14 The content of the phase is controlled at 80-100%, and the volume density of ZrO2-doped CMA is controlled at 2.0-3.17 g / cm 3 The porosity is controlled between 45.5% and 10.4%, the water absorption is between 20.8% and 3.4%, and the melting point is increased by more than 10°C.

[0012] Furthermore, in some embodiments of the method for preparing ZrO2-doped CMA materials and integrating structural and functional control thereof, in step S1, the average particle size of the aluminum oxide source is not greater than 56 μm, the average particle size of the magnesium oxide source is not greater than 56 μm, the average particle size of the calcium oxide source is not greater than 56 μm, and the average particle size of zirconium dioxide is not greater than 6 μm.

[0013] Some embodiments disclose a method for preparing ZrO2-doped CMA materials and integrating their structural and functional control. In step S1, the aluminum oxide source is Al2O3, the calcium oxide source is CaCO3, and the magnesium oxide source is MgO; wherein the mass ratio of Al2O3, CaCO3, and MgO is 83.56-85.29:11.72-11.75:4.72-2.96.

[0014] Some embodiments disclose a method for preparing a ZrO2-doped CMA material and integrating its structure and function. In step S1, the aluminum oxide source is Al2O3, the calcium oxide source is CaO, and the magnesium oxide source is MgO, wherein the mass ratio of Al2O3, CaO, and MgO is 88.83-89.94:6.94:4.23-3.12.

[0015] Some embodiments disclose a method for preparing a ZrO2-doped CMA material and integrating its structural function. In step S1, the aluminum oxide source is Al2O3, the calcium oxide source is CaO, and the magnesium oxide source is Mg(OH)2, wherein the mass ratio of Al2O3, CaO, and Mg(OH)2 is 86.18-88.70: 6.78-6.85: 7.04-4.45.

[0016] Some embodiments disclose a method for preparing ZrO2-doped CMA materials and integrating their structural and functional control. In step S1, the aluminum oxide source is Al2O3, the calcium oxide source is CaO, and the magnesium oxide source is MgCO3, wherein the mass ratio of Al2O3, CaO, and MgCO3 is 83.56-86.98: 6.57-6.71: 9.87-6.31.

[0017] Some embodiments disclose a method for preparing ZrO2-doped CMA materials and integrating their structural and functional control. In step S1, the aluminum oxide source is Al2O3, the calcium oxide source is CaCO3, and the magnesium oxide source is MgCO3, wherein the mass ratio of Al2O3, CaCO3, and MgCO3 is 79.47-82.62:11.14-11.38:9.39-6.00.

[0018] Some embodiments disclose a method for preparing a ZrO2-doped CMA material and integrating its structure and function. In step S1, the aluminum oxide source is Al2O3, the calcium oxide source is CaCO3, and the magnesium oxide source is Mg(OH)2, wherein the mass ratio of Al2O3, Ca CO3, and Mg(OH)2 is 81.83-84.18:11.48-11:60:6.69-4.22.

[0019] On the other hand, some embodiments disclose a ZrO2-doped CMA material, which is obtained by preparing a ZrO2-doped CMA material and a method for integrating structure and function, wherein the ZrO2-doped CMA material contains only C2M2A 14 and CM2A8 phases, Zr ions are uniformly distributed in CMA grains; C2M2A 14 The content of phase is 80-100%, and the volume density of ZrO2-doped CMA is 2.0-3.17 g / cm 3 The porosity is between 45.5% and 10.4%, the water absorption is between 20.8% and 3.4%, and the melting point is increased by more than 10°C.

[0020] Some embodiments disclose ZrO2-doped CMA materials, which are used as refractory materials, wherein C2M2A 14 The ZrO2-doped CMA material with relatively high phase content is used as the thermal insulation material of industrial furnaces, C2M2A 14 ZrO2-doped CMA materials with relatively low phase content are used as working layer materials for industrial furnaces.

[0021] The ZrO2-doped CMA material preparation and its structure and function integrated control method disclosed in the embodiment of the present invention adopts a one-step sintering method to prepare a ZrO2-doped CMA material with adjustable performance, which has a short production cycle and low production cost; the CMA material contains only C2M2A 14 The C2M2A8 phase in the CMA material can be controlled by adjusting the ZrO2 doping amount, sintering temperature and holding time. 14 The phase content is regulated between 80% and 100%, and Zr ions are evenly distributed in the CMA grains. The volume density of CMA can be achieved between 2.0 and 3.17 g / cm 3The porosity is regulated between 45.5% and 10.4%, the water absorption is regulated between 20.8% and 3.4%, and the melting point is increased by more than 10°C; ZrO2-doped CMA can be used to prepare refractory materials with excellent performance; by regulating the C2M2A in ZrO2-doped CMA materials 14 Precise control of the phase content can achieve integrated regulation of the structure and function of the CMA material, and obtain refractory materials with different densities. Through the combined use of CMA materials with different densities, they can be applied to different parts of the furnace body of an industrial boiler. The preparation method of ZrO2-doped CMA material and the method for integrated regulation of its structure and function disclosed in the embodiment of the present invention have good application prospects in the industrial preparation of CMA materials and the field of refractory materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a flow chart for preparing the ZrO2-doped CMA material disclosed in Example 1;

[0023] Figure 2 The XRD spectrum of the CMA material doped with ZrO2 having a content of 1.5 wt% disclosed in Example 2;

[0024] Figure 3 The XRD spectrum of the CMA material doped with ZrO2 having a content of 1.3 wt% disclosed in Example 3;

[0025] Figure 4 is a SEM image of the CMA surface disclosed in Comparative Example 1;

[0026] Figure 5 is a SEM image of the CMA surface disclosed in Example 4;

[0027] Figure 6 is the XRD pattern of the CMA surface disclosed in Example 4;

[0028] Figure 7 is a SEM image of the CMA surface disclosed in Example 5;

[0029] Figure 8 is the XRD pattern of the CMA surface disclosed in Example 5;

[0030] Fig. 9 This is a cross-sectional scan image of the ZrO2-doped CMA (1.5wt% ZrO2) material in Example 2. DETAILED DESCRIPTION

[0031] The word "embodiment" used herein as an "exemplary" does not necessarily mean that any embodiment described is superior or better than other embodiments. Performance index tests in the embodiments of the present invention are performed using conventional test methods in the art unless otherwise specified. It should be understood that the terms described in the embodiments of the present invention are only used to describe specific implementation methods and are not intended to limit the contents disclosed in the embodiments of the present invention.

[0032] Unless otherwise specified, the technical and scientific terms used herein have the same meanings as commonly understood by ordinary technicians in the technical field to which the embodiments of the present invention belong; other experimental methods and technical means not specifically specified in the embodiments of the present invention refer to experimental methods and technical means commonly used by ordinary technicians in the field.

[0033] The terms "substantially" and "approximately" used herein are used to describe small fluctuations. For example, they can refer to less than or equal to ±5%, such as less than or equal to ±2%, such as less than or equal to ±1%, such as less than or equal to ±0.5%, such as less than or equal to ±0.2%, such as less than or equal to ±0.1%, such as less than or equal to ±0.05%. The numerical data represented or presented in the range format herein are used only for convenience and brevity, and should therefore be flexibly interpreted as including not only the values ​​clearly listed as the limits of the range, but also all independent values ​​or sub-ranges contained in the range. For example, the numerical range of "1-5%" should be interpreted as including not only the clearly listed values ​​of 1% to 5%, but also the independent values ​​and sub-ranges within the range shown. Therefore, independent values ​​such as 2%, 3.5% and 4% and sub-ranges such as 1%-3%, 2%-4% and 3%-5% are included in this numerical range. This principle also applies to the range of only one numerical value. In addition, such an interpretation applies regardless of the width of the range or the characteristics described.

[0034] In this document, including in the claims, transitional words such as "comprises," "includes," "with," "having," "containing," "involving," "accommodating," etc. are understood to be open-ended, i.e., meaning "including but not limited to." Only the transitional words "consisting of" and "composed of" are closed transitional words.

[0035] In order to better illustrate the present invention, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the gist of the present invention.

[0036] Under the premise of no conflict, the technical features disclosed in the embodiments of the present invention can be arbitrarily combined, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present invention.

[0037] C2M2A 14 It has a hexagonal plate / flake morphology, and CM2A8 presents an equiaxed morphology. The difference in grain morphology further affects the physical properties of the prepared samples. In the process of reacting to form CMA, the route followed is CA6→C2M2A 14 →CM2A8, inevitably in the preparation of C2M2A 14 The CM2A8 phase is produced in the process. By controlling the content of the two phases and utilizing the different grain morphologies of the two phases, the physical properties of the prepared samples are adjusted to achieve integrated regulation of the structure and function of the CMA material. The prepared ZrO2-doped CMA materials of different densities can be used in combination and can be applied to different parts of the industrial boiler furnace body.

[0038] The technical solution provided by the embodiment of the present invention is based on the coordinated regulation of the content of the phase in the CMA material by ZrO2 doping, firing temperature and holding time. The physical phase composition content and physical properties of the prepared ZrO2 doped CMA material are regulated by adjusting the amount of ZrO2 added in the raw material, the firing temperature and the holding time, so that ZrO2 doped CMA materials with different densities are prepared respectively. The ZrO2 doped CMA materials with different densities can be used in combination. The ZrO2 doped CMA material, as a refractory material with different properties, can be applied to different parts of the furnace body of an industrial boiler. By adjusting the physical phase in the ZrO2 doped CMA, the application of the ZrO2 doped CMA material in different fields can also be met.

[0039] In some embodiments, the method for preparing ZrO2-doped CMA materials and integrating their structure and function comprises the following steps:

[0040] S1, an alumina source, a calcium oxide source and a magnesium oxide source are mixed in a set ratio to obtain a mixed source material, an additive zirconium dioxide is added to the mixed raw material, and a mixer is used to mix the raw material mixture; wherein the particle sizes of the alumina source, the calcium oxide source and the magnesium oxide source are equivalent, the mass ratio of zirconium dioxide to the mixed source material is not more than 4%, and the mixing time of the mixer is 1-6 hours; generally, the doped Zr atoms replace the positions of the Al atoms and are integrated into the C2M2Al 14 or CM2A8 grains, it can increase the thickness of the grains in the ZrO2-doped CMA material, thereby reducing the pores inside the sample, increasing the density of the sample, and facilitating the densification of the product;

[0041] Generally, the uniformity of the mixing of the three raw materials of alumina source, calcium oxide source and magnesium oxide source determines the purity of the prepared CMA material. Uneven mixing of the raw materials may lead to element enrichment in some areas, making it inconsistent with the optimal atomic ratio of CMA, thereby producing impurity phases such as calcium dialuminate, calcium hexaaluminate and magnesium aluminum spinel, resulting in impure CMA samples. Therefore, the raw material mixture needs to be fully stirred and mixed to obtain a uniform mixed material.

[0042] Generally, the alumina source is industrial alumina, activated alumina or calcined alumina; the calcium oxide source is calcium oxide or calcium carbonate, and the magnesium oxide source is magnesium oxide, magnesium hydroxide or magnesium carbonate; generally, the particle sizes of the alumina source, magnesium source and calcium source have a significant effect on the physical properties and purity of the prepared CMA. If the particle sizes of the three raw materials are too different, segregation will occur during the mixing process, thereby affecting the purity of the synthesized CMA. Therefore, the particle sizes of the three raw materials are usually equivalent and the particle size distribution range is close; for example, the average particle size of the alumina source is not more than 56μm, the average particle size of the magnesium oxide source is not more than 56μm, and the average particle size of the calcium oxide source is not more than 56μm; at the same time, the particle size of zirconium oxide is smaller than that of the alumina source, calcium oxide source or magnesium oxide source, for example, the average particle size of ZrO2 is not more than 6μm;

[0043] S2, stirring and mixing the raw material mixture, adding a water binder, and obtaining a uniformly mixed material; wherein the mass ratio of water to the raw material mixture is 5 to 50%;

[0044] Generally, the amount of water added determines the uniformity of its dispersion in the mixed powder. Too little or too much water will cause excessive accumulation of water in some areas. During the drying process, the water evaporates due to heat, which will produce holes at its location, thus affecting the physical properties of the prepared CMA. Too little water may cause the mixed powder to be stratified or not formed during the pressing process. Generally, the mass ratio of water to raw material mixture is 5-50%.

[0045] S3, the uniformly mixed material is pressed and molded at a pressure of 80-120 MPa to obtain a green body;

[0046] Usually, the uniformly mixed materials can be molded under the pressure of a press. The pressure of the press has an important influence on the quality of the green body after molding. If the pressure is too high, it may cause stratification inside the green body, affecting the physical properties of the prepared CMA; if the pressure is too low, it may make the green body difficult to mold. The appropriate pressure range is 80-120MPa.

[0047] S4, the green body is fired at 1650-1750℃ in air atmosphere and kept at this temperature for 3-10h to obtain ZrO2-doped CMA material. ZrO2-doped CMA material contains only C2M2A 14and CM2A8 phases, Zr ions are uniformly distributed in the CMA grains; 14 The content of the phase is controlled at 80-100%, and the bulk density of CMA is controlled at 2.0-3.17 g / cm 3 The porosity is controlled between 45.5% and 10.4%, the water absorption is between 20.8% and 3.4%, and the melting point is increased by more than 10°C.

[0048] Generally, the firing temperature of ZrO2-doped CMA materials has an important influence on the performance of the product; if the firing temperature is too low or the holding time is too short, the product may not react completely, thus affecting the purity and physical properties of the prepared ZrO2-doped CMA; if the firing temperature is too high or the holding time is too long, the grains of the prepared ZrO2-doped CMA may be too large, thus affecting the further application of ZrO2-doped CMA. Therefore, under the condition of controlling the amount of ZrO2 added, the C2M2A content in the product can be adjusted by adjusting the firing temperature and the holding time. 14 The content of phase and the physical properties of the sample, increasing the sintering temperature or extending the holding time can inhibit the C2M2A in CMA 14 The formation of phases and the preparation of high-density CMA materials can be applied to the working layer of industrial furnace linings;

[0049] Some embodiments disclose a method for preparing ZrO2-doped CMA materials and integrating their structure and function, wherein the aluminum oxide source is Al2O3, the calcium oxide source is CaCO3, and the magnesium oxide source is MgO; wherein the mass ratio of Al2O3, CaCO3, and MgO is 83.56-85.29:11.72-11.75:4.72-2.96. Generally, ZrO2-doped CMA materials are directly prepared using Al2O3, CaCO3, and MgO raw materials. During the reaction, CaCO3 decomposes to produce CO2, which may produce pores inside the sample, thereby increasing the porosity of the ZrO2-doped CMA material and reducing the material density. The ZrO2-doped CMA material prepared by this method can be applied to the production of ZrO2-doped CMA fine powder and industrial furnace lining insulation layer.

[0050] In some embodiments, the preparation of ZrO2-doped CMA materials and the integrated control method of their structure and function are disclosed, wherein the aluminum oxide source is Al2O3, the calcium oxide source is CaO, and the magnesium oxide source is MgO, wherein the mass ratio of Al2O3, CaO, and MgO is 88.83-89.94:6.94:4.23-3.12. Generally, ZrO2-doped CMA materials are prepared directly using Al2O3, CaO, and MgO raw materials. During the reaction, the raw materials will not decompose, and ZrO2-doped CMA materials with low porosity and high density can be prepared, which can be applied to the production of ZrO2-doped CMA aggregates and working layer materials of industrial furnace linings.

[0051] Some embodiments disclose a method for preparing a ZrO2-doped CMA material and integrating its structure and function, wherein the aluminum oxide source is Al2O3, the calcium oxide source is CaO, and the magnesium oxide source is Mg(OH)2, wherein the mass ratio of Al2O3, CaO, and Mg(OH)2 is 86.18-88.70:6.78-6.85:7.04-4.45. Generally, Al2O3, CaO, and Mg(OH)2 are directly used as raw materials to prepare a ZrO2-doped CMA material. During the reaction, Mg(OH)2 decomposes to produce H2O, which may produce pores and cracks inside the sample, thereby increasing the porosity of the ZrO2-doped CMA material and reducing the gas density. The presence of cracks is conducive to the crushing of the ZrO2-doped CMA material. The ZrO2-doped CMA material prepared by this method can be applied to the production of ZrO2-doped CMA fine powder and industrial furnace lining insulation layer.

[0052] Some embodiments disclose a method for preparing a ZrO2-doped CMA material and integrating its structure and function, wherein the aluminum oxide source is Al2O3, the calcium oxide source is CaO, and the magnesium oxide source is MgCO3, wherein the mass ratio of Al2O3, CaO, and MgCO3 is 83.56-86.98: 6.57-6.71: 9.87-6.31. Generally, the ZrO2-doped CMA material is directly prepared using Al2O3, CaO, and MgCO3 raw materials. During the reaction, MgCO3 decomposes to produce CO2, which may generate pores inside the sample, thereby increasing the porosity of the ZrO2-doped CMA material and reducing its density. The ZrO2-doped CMA material prepared by this method can be applied to the production of ZrO2-doped CMA fine powder and industrial furnace lining insulation layer.

[0053] Some embodiments disclose a method for preparing a ZrO2-doped CMA material and integrating its structure and function, wherein the aluminum oxide source is Al2O3, the calcium oxide source is CaCO3, and the magnesium oxide source is MgCO3, wherein the mass ratio of Al2O3, CaCO3, and MgCO3 is 79.47-82.62:11.14-11.38:9.39-6.00. Generally, the ZrO2-doped CMA material is directly prepared using Al2O3, CaCO3, and MgCO3 raw materials. During the reaction, CaCO3 and MgCO3 decompose to produce CO2, which may generate pores inside the sample, thereby increasing the porosity of the ZrO2-doped CMA material and reducing the gas density. The ZrO2-doped CMA material prepared by this method can be applied to the production of ZrO2-doped CMA fine powder and industrial furnace lining insulation layer.

[0054] Some embodiments disclose a method for preparing a ZrO2-doped CMA material and integrating its structure and function, wherein the aluminum oxide source is Al2O3, the calcium oxide source is CaCO3, and the magnesium oxide source is Mg(OH)2, wherein the mass ratio of Al2O3, CaCO3, and Mg(OH)2 is 81.83-84.18:11.48-11:60:6.69-4.22. Generally, Al2O3, CaCO3, and Mg(OH)2 are directly used as raw materials to prepare a ZrO2-doped CMA material. During the reaction, CaCO3 and Mg(OH)2 decompose to produce CO2 and H2O, which may generate pores and cracks inside the sample, thereby increasing the porosity of the CMA material and reducing its density. The presence of cracks is conducive to the crushing of the ZrO2-doped CMA material. The ZrO2-doped CMA material prepared by this method can be applied to the production of ZrO2-doped CMA fine powder and industrial furnace lining insulation layer.

[0055] The ZrO2-doped CMA material disclosed in some embodiments is obtained by preparing the ZrO2-doped CMA material and its structure and function integrated control method, and the ZrO2-doped CMA material contains only C2M2A 14 and CM2A8 phases, Zr ions are uniformly distributed in CMA grains; C2M2A 14 The content of phase is 80-100%, and the volume density of ZrO2-doped CMA is 2.0-3.17 g / cm 3 The porosity is between 45.5% and 10.4%, the water absorption is between 20.8% and 3.4%, and the melting point is increased by more than 10°C.

[0056] Some embodiments disclose ZrO2-doped CMA materials, which are used as refractory materials, wherein C2M2A 14 The ZrO2-doped CMA material with relatively high phase content is used as the thermal insulation material of industrial furnaces, C2M2A14 ZrO2-doped CMA materials with relatively low phase content are used as working layer materials for industrial furnaces. Generally, when ZrO2-doped CMA materials are used as refractory materials, C2M2A 14 The content of the phase can be adjusted between 80% and 100%, and the preparation of C2M2A can be controlled according to the requirements of refractory performance. 14 The content of phase will be different C2M2A 14 Phase content of refractory materials are used in combination to construct the structure of industrial boiler furnace body; generally, in the structure of industrial boiler furnace body, ZrO2 doped CMA material as thermal insulation material, C2M2A 14 The content of phase is higher than that of C2M2A in the working layer material 14 Phase content; for example, C2M2A 14 ZrO2-doped CMA materials with a phase content between 95% and 100% can be used as thermal insulation materials for industrial furnaces; C2M2A 14 ZrO2 doped CMA material with a phase content between 80% and 90% can be used as a working layer material for industrial furnaces.

[0057] Some embodiments disclose the application of ZrO2-doped CMA materials. ZrO2-doped CMA materials can be used to prepare ZrO2-doped CMA dense refractory products, porous refractory products, aggregates and fine powders. Aggregates and fine powders can be further used to prepare CMA crucibles, added as additives to magnesium-carbon refractory materials, or used as surface materials for mold shells.

[0058] The technical details are further illustrated below in conjunction with embodiments.

[0059] Example 1

[0060] In Example 1, Figure 1 As shown, the preparation method of ZrO2-doped CMA material and its integrated structural function regulation method include the following steps:

[0061] S1, an aluminum oxide source, a calcium oxide source and a magnesium oxide source are mixed in a set ratio to obtain a mixed source material, an additive zirconium dioxide is added to the mixed raw material, and a mixer is used to mix the raw material mixture to obtain a raw material mixture; wherein the particle sizes of the aluminum oxide source, the calcium oxide source and the magnesium oxide source are equivalent, the mass ratio of zirconium dioxide to the mixed source material is not more than 4%, and the mixing time of the mixer is 1-6 hours;

[0062] S2, stirring and mixing the raw material mixture, adding a water binder, and obtaining a uniformly mixed material; wherein the mass ratio of water to the raw material mixture is 5 to 50%;

[0063] S3, the uniformly mixed material is pressed and molded at a pressure of 80-120 MPa to obtain a green body;

[0064] S4. The green body is fired at 1650-1750° C. in an air atmosphere and kept at this temperature for 3-10 hours to obtain a ZrO2-doped CMA material.

[0065] Example 2

[0066] In Example 2, the preparation method of ZrO2-doped CMA material and its integrated structural function control method include the following steps:

[0067] S1, an aluminum oxide source, a calcium oxide source and a magnesium oxide source are mixed in a set ratio to obtain a mixed source material, an additive zirconium dioxide is added to the mixed raw material, and a mixer is used to mix the raw material mixture to obtain a raw material mixture; wherein the particle sizes of the aluminum oxide source, the calcium oxide source and the magnesium oxide source are equivalent, the mass ratio of zirconium dioxide to the mixed source material is 1.5%, and the mixing time of the mixer is 1 hour;

[0068] S2, stirring and mixing the raw material mixture, adding a water binder, and obtaining a uniformly mixed material; wherein the mass ratio of water to the raw material mixture is 5%;

[0069] S3, the uniformly mixed materials are pressed under a pressure of 120 MPa to obtain a green body;

[0070] S4. The green body is fired at 1700°C in an air atmosphere and kept warm for 6 hours to obtain a ZrO2-doped CMA material.

[0071] Figure 2 This is the XRD pattern of the CMA material doped with ZrO2 content of 1.5 wt% disclosed in Example 2. Figure 6 This is a cross-sectional scan image of the CMA material doped with ZrO2 having a content of 1.5 wt% in Example 2.

[0072] Example 3

[0073] In Example 3, the method for preparing ZrO2-doped CMA materials and integrating their structure and function includes the following steps:

[0074] S1, an aluminum oxide source, a calcium oxide source and a magnesium oxide source are mixed in a set ratio to obtain a mixed raw material, an additive zirconium dioxide is added to the mixed raw material, and a mixer is used to mix the raw material mixture uniformly; wherein the particle sizes of the aluminum oxide source, the calcium oxide source and the magnesium oxide source are equivalent, the mass ratio of zirconium dioxide to the mixed source material is 1.3%, and the mixing time of the mixer is 2 hours;

[0075] S2, stirring and mixing the raw material mixture, adding a water binder, and obtaining a uniformly mixed material; wherein the mass ratio of water to the raw material mixture is 5%;

[0076] S3, the uniformly mixed materials are pressed under a pressure of 100 MPa to obtain a green body;

[0077] S4. The green body is fired at 1650°C in an air atmosphere and kept warm for 3 hours to obtain a ZrO2-doped CMA material.

[0078] Figure 3 This is the XRD spectrum of the CMA material doped with ZrO2 with a content of 1.3 wt% disclosed in Example 3.

[0079] Example 4

[0080] In Example 4, the method for preparing ZrO2-doped CMA materials and integrating their structure and function includes the following steps:

[0081] S1, an aluminum oxide source, a calcium oxide source and a magnesium oxide source are mixed in a set ratio to obtain a mixed source material, an additive zirconium dioxide is added to the mixed raw material, and a mixer is used to mix the raw material mixture to obtain a raw material mixture; wherein the particle sizes of the aluminum oxide source, the calcium oxide source and the magnesium oxide source are equivalent, the mass ratio of zirconium dioxide to the mixed source material is 1.3%, and the mixing time of the mixer is 2 hours;

[0082] S2, stirring and mixing the raw material mixture, adding a water binder, and obtaining a uniformly mixed material; wherein the mass ratio of water to the raw material mixture is 5%;

[0083] S3, the uniformly mixed materials are pressed under a pressure of 100 MPa to obtain a green body;

[0084] S4. The green body is fired at 1750°C in an air atmosphere and kept warm for 10 hours to obtain a ZrO2-doped CMA material.

[0085] Figure 5 This is the SEM image of the CMA material doped with ZrO2 with a content of 1.3 wt% disclosed in Example 4.

[0086] Figure 6 The XRD spectrum of the CMA material doped with ZrO2 with a content of 1.3 wt% disclosed in Example 4. According to the RIR method for calculating the phase content, it can be seen that the C2M2A in the ZrO2-doped CMA material obtained in Example 4 is 14 The phase content is 80%, the CM2A8 phase content is 20%, the internal grains are equiaxed, and the volume density of the sample measured by the Archimedean drainage method is 3.15g / cm 3 The porosity is 10.76% and the water absorption is 3.25%. The high-density ZrO2-doped CMA material prepared by this method can be used for the working layer of the furnace body.

[0087] Example 5

[0088] In Example 5, the preparation method of ZrO2-doped CMA material and its structural function integrated control method include the following steps:

[0089] S1, an aluminum oxide source, a calcium oxide source and a magnesium oxide source are mixed in a set ratio to obtain a mixed source material, an additive zirconium dioxide is added to the mixed raw material, and a mixer is used to mix the raw material mixture to obtain a raw material mixture; wherein the particle sizes of the aluminum oxide source, the calcium oxide source and the magnesium oxide source are equivalent, the mass ratio of zirconium dioxide to the mixed source material is 2.5%, and the mixing time of the mixer is 5 hours;

[0090] S2, stirring and mixing the raw material mixture, adding a water binder, and obtaining a uniformly mixed material; wherein the mass ratio of water to the raw material mixture is 5%;

[0091] S3, the uniformly mixed materials are pressed under a pressure of 100 MPa to obtain a green body;

[0092] S4. The green body is fired at 1680°C in an air atmosphere and kept warm for 6 hours to obtain a ZrO2-doped CMA material.

[0093] Figure 7 This is the SEM image of the CMA material doped with ZrO2 with a content of 2.5 wt% disclosed in Example 5.

[0094] Figure 8 The XRD spectrum of the CMA material doped with ZrO2 with a content of 2.5 wt% disclosed in Example 5 shows that the ZrO2-doped CMA material prepared in Example 5 contains only C2M2A 14 The internal grains are flaky and contain abundant pores. The volume density of the sample measured by Archimedes drainage method is 2.11 g / cm 3 The porosity is 43.5%, and the water absorption is 18.84%. The porous CMA material prepared under this condition can be used as the heat insulation layer of the furnace body.

[0095] Comparative Example 1

[0096] In Comparative Example 1, the industrial preparation method of CMA material includes the following steps:

[0097] S1, an aluminum oxide source, a calcium oxide source and a magnesium oxide source are mixed in a set ratio to obtain a mixed source material, and a mixer is used to mix the mixed source material to obtain a raw material mixture; wherein the particle sizes of the aluminum oxide source, the calcium oxide source and the magnesium oxide source are equivalent, and the mixing time of the mixer is 1 hour;

[0098] S2, stirring and mixing the raw material mixture, adding a water binder, and obtaining a uniformly mixed material; wherein the mass ratio of water to the raw material mixture is 5%;

[0099] S3, the uniformly mixed materials are pressed under a pressure of 120 MPa to obtain a green body;

[0100] S4. The green body is fired at 1700°C in an air atmosphere and kept at this temperature for 6 hours to obtain a CMA material.

[0101] Fig. 9 : is a SEM image of the CMA surface disclosed in Comparative Example 1. Fig. 9 As shown, the internal grains of the CMA material prepared without doped ZrO2 are flaky and have a certain pore structure.

[0102] The technical solutions disclosed in the embodiments of the present invention and the technical details disclosed in the embodiments are merely illustrative of the inventive concept of the present invention and do not constitute a limitation on the technical solutions of the embodiments of the present invention. Any conventional changes, replacements or combinations of the technical details disclosed in the embodiments of the present invention have the same inventive concept as the present invention and are within the protection scope of the claims of the present invention.

Claims

1. Preparation of ZrO2-doped CMA materials and integrated structural and functional control method, characterized in that: Includes steps: S1, an aluminum oxide source, a calcium oxide source and a magnesium oxide source are mixed in a set ratio to obtain a mixed source material, an additive zirconium dioxide is added to the mixed raw material, and a mixer is used to mix the raw material mixture to obtain a raw material mixture; wherein the particle sizes of the aluminum oxide source, the calcium oxide source and the magnesium oxide source are equivalent, the mass ratio of the zirconium dioxide to the mixed source material is not more than 4wt%, and the mixing time of the mixer is 1 to 6h; S2, stirring and mixing the raw material mixture, adding a water binder, and obtaining a uniformly mixed material; wherein the mass ratio of water to the raw material mixture is 5 to 50%; S3, the uniformly mixed material is pressed and molded at a pressure of 80-120 MPa to obtain a green body; S4, firing the green body at 1650-1750° C. in an air atmosphere for 3-10 hours to obtain a ZrO2-doped CMA material; The ZrO2-doped CMA material contains only C2M2A 14 and CM2A8 phases, Zr ions are uniformly distributed in the CMA grains; the C2M2A 14 The content of the phase is controlled at 80-100%; the volume density of the ZrO2-doped CMA is controlled at 2.0-3.17 g / cm 3 The porosity is controlled between 45.5% and 10.4%, the water absorption is between 20.8% and 3.4%, and the melting point is increased by more than 10°C.

2. The method for preparing ZrO2-doped CMA materials and integrating their structure and function according to claim 1 is characterized in that: In step S1, the average particle size of the aluminum oxide source is not greater than 56 μm, the average particle size of the magnesium oxide source is not greater than 56 μm, the average particle size of the calcium oxide source is not greater than 56 μm, and the average particle size of the zirconium dioxide is not greater than 6 μm.

3. The method for preparing ZrO2-doped CMA materials and integrating structure and function control thereof according to claim 1, characterized in that: In step S1, the aluminum oxide source is Al2O3, the calcium oxide source is CaCO3, and the magnesium oxide source is MgO; Among them, Al2O 3、 The mass ratio of CaCO3 and MgO is 83.56~85.29:11.72~11.75:4.72~2.

96.

4. The method for preparing ZrO2-doped CMA materials and integrating structure and function control thereof according to claim 1, characterized in that: In step S1, the aluminum oxide source is Al2O3, the calcium oxide source is CaO, and the magnesium oxide source is MgO, wherein the mass ratio of Al2O3, CaO, and MgO is 88.83-89.94:6.94:4.23-3.

12.

5. The method for preparing ZrO2-doped CMA material and integrating structure and function control thereof according to claim 1, characterized in that: In step S1, the aluminum oxide source is Al2O3, the calcium oxide source is CaO, and the magnesium oxide source is Mg(OH)2, wherein the mass ratio of Al2O3, CaO, and Mg(OH)2 is 86.18-88.70:6.78-6.85:7.04-4.

45.

6. The method for preparing ZrO2-doped CMA material and integrating structure and function control thereof according to claim 1, characterized in that: In step S1, the aluminum oxide source is Al2O3, the calcium oxide source is CaO, and the magnesium oxide source is MgCO3, wherein the mass ratio of Al2O3, CaO, and MgCO3 is 83.56-86.98:6.57-6.71:9.87-6.

31.

7. The method for preparing ZrO2-doped CMA material and integrating structure and function control thereof according to claim 1, characterized in that: In step S1, the aluminum oxide source is Al2O3, the calcium oxide source is CaCO3, and the magnesium oxide source is MgCO3, wherein the mass ratio of Al2O3, CaCO3, and MgCO3 is 79.47-82.62:11.14-11.38:9.39-6.

00.

8. The method for preparing ZrO2-doped CMA material and integrating structure and function control thereof according to claim 1, characterized in that: In step S1, the aluminum oxide source is Al2O3, the calcium oxide source is CaCO3, and the magnesium oxide source is Mg(OH)2, wherein the mass ratio of Al2O3, CaCO3, and Mg(OH)2 is 81.83-84.18:11.48-11:60:6.69-4.

22.

9. ZrO2 doped CMA material, characterized in that The method for preparing the ZrO2-doped CMA material and integrating its structure and function is obtained by any one of claims 1 to 8, wherein the CMA material contains only C2M2A 14 and CM2A8 phases, Zr ions are uniformly distributed in the CMA grains; 14 The content of the phase is 80-100%, and the volume density of CMA is 2.0-3.17 g / cm 3 The porosity is between 45.5% and 10.4%, the water absorption is between 20.8% and 3.4%, and the melting point is increased by more than 10°C.

10. The ZrO2-doped CMA material according to claim 9, characterized in that: ZrO2 doped CMA materials are used as refractory materials, among which C2M2A 14 The ZrO2-doped CMA material with relatively high phase content is used as the thermal insulation material of industrial furnaces, C2M2A 14 ZrO2-doped CMA materials with relatively low phase content are used as working layer materials for industrial furnaces.

Citation Information

Patent Citations

  • Compact aluminum-magnesium-calcium fire-resistant clinker and preparation method thereof

    CN104671810A

  • Preparation method of nano oxide enhanced aluminum oxide-magnesium oxide-calcium oxide composite material

    CN107399959A

  • Industrial preparation method of CMA material for regulating and controlling crystal morphology of raw material based on MgO

    CN114560687A

  • Refractory material with molten steel cleaning function as well as preparation method and application thereof

    CN115321967A

  • Refractory material with function of cleaning molten steel, preparation method therefor and use thereof

    US20240261851A1

Cited By

  • Preparation method of novel ceramic filter for nickel-based superalloy melt pouring

    CN120664897A

  • High-density CMA refractory material and preparation method thereof

    CN121850636A

  • A high-density CMA refractory material and its preparation method

    CN121850636B